Analysis of Bacillus cereus cell viability, sublethal injury, and death induced by mild thermal treatment. Issue 1 (25th November 2018) - Lv, Ruiling; Wang, Danli; Zou, Mingming; Wang, Wenjun; Ma, Xiaobin; Chen, Weijun; Zhou, Jianwei; Ding, Tian; Ye, Xingqian; Liu, Donghong
Abstract: As the most cost‐effective tool to ensure microbial safety, thermal processing induces a large portion of sublethal injury presenting a potential hazard to food safety. Thermal treatment at 63 °C for 1 min injured 2.22 log cfu/ml totally, half of which were sublethally injured using plate counting method. After 2 min, the inactivation log of Bacillus cereus reached 1.55 while the sublethally injured log even reached 2.16. As for the sublethally injured rate of the B. cereus, it was over 65% after 0.5 min and kept ever‐increase with time. In the end, the injured rate arrived at 99.30% after 2 min processing time. Partial esterase enzyme inactivation was found after 0.5 min heat treatment with flow cytometry combining carboxyfluorescein diacetate/propidium iodide (PI) double‐staining, but B. cereus was not dyed by PI at 63 °C. Comparing with the initial protein concentration of 0.57 ± 0.02 μg/ml, the leakage of the protein was not so notable though the general trend was increasing with duration of heat. Scanning and transmission electron microscopy analysis revealed that a portion of cells morphology and structure had changed after thermal process. Practical applications: Bacillus cereus is an endospore forming pathogenic, causing foodborne illnesses and outbreaks all over the world. This research indicated that thermal treatment at 63 °C was a sublethal stress for B. cereus that a portion of cells were sublethally injured which could resume growth in suitable condition and might exist potential safety hazard if used for food pasteurization.